The Effect of Timeliness of Financial Reporting on Abnormal Return during the Covid-19 Period with Profitability and Company Size as Moderating Variables (Study on the Food and Beverages Sector Companies Listed on the IDX in 2020-2021) - Sella Yunita; Agrianti Komalasari; Saring Suhendro (International Journal of Business and Applied Economics, 2023)
The COVID-19 pandemic situation that occurred globally has significantly affected all aspects, one of which is the timeliness of submitting financial reports. The purpose of this study was to determine whether there is an effect of timeliness of financial reporting on abnormal returns and whether profitability and company size can affect the relationship between timeliness of financial reporting and abnormal returns. This study uses secondary data obtained from financial reports and independent auditor reports published on the official website of the Indonesia Stock Exchange. The data analysis techniques used in this study are descriptive statistics and moderated regression analysis (MRA). The results of this study indicate that the timeliness of financial reporting affects abnormal returns, while profitability and company size do not strengthen the relationship between timeliness of financial reporting and abnormal returns during the COVID-19 period.